2020
DOI: 10.3390/antiox9030195
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of MitoVitE, α-Tocopherol and Trolox on Oxidative Stress, Mitochondrial Function and Inflammatory Signalling Pathways in Endothelial Cells Cultured under Conditions Mimicking Sepsis

Abstract: Sepsis is a life-threatening response to infection associated with inflammation, oxidative stress and mitochondrial dysfunction. We investigated differential effects of three forms of vitamin E, which accumulate in different cellular compartments, on oxidative stress, mitochondrial function, mRNA and protein expression profiles associated with the human Toll-like receptor (TLR) -2 and -4 pathways. Human endothelial cells were exposed to lipopolysaccharide (LPS)/peptidoglycan G (PepG) to mimic sepsis, MitoVitE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
(98 reference statements)
4
20
0
Order By: Relevance
“…Hegarty and Byrne are correct in that there are other biologically active forms of tocopherol; however, α-tocopherol is the most abundant in the body and therefore arguably the most important and a good choice for comparison, although we concur that investigating the relative effects of other tocopherols and tocotrienols would have been interesting. We agree that MitoVitE has been shown to be more protective than Trolox; nevertheless, it has been demonstrated that Trolox has potent antioxidant activity in several different models (references 7–9 in our paper [ 3 ]). We expected Trolox to be of less benefit than MitoVitE under conditions of sepsis in our model, but that was not what we found.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Hegarty and Byrne are correct in that there are other biologically active forms of tocopherol; however, α-tocopherol is the most abundant in the body and therefore arguably the most important and a good choice for comparison, although we concur that investigating the relative effects of other tocopherols and tocotrienols would have been interesting. We agree that MitoVitE has been shown to be more protective than Trolox; nevertheless, it has been demonstrated that Trolox has potent antioxidant activity in several different models (references 7–9 in our paper [ 3 ]). We expected Trolox to be of less benefit than MitoVitE under conditions of sepsis in our model, but that was not what we found.…”
supporting
confidence: 79%
“…In our study [ 3 ], we used carboxy-DCFDA to measure the overall total cellular ROS production. Hegarty and Byrne suggest that we could have also used a mitochondrial-specific dye such as MitoSOX red.…”
mentioning
confidence: 99%
“…An in vitro sepsis model showed that vitamin E (α tocopherol), Trolox (soluble vitamin E), and motVit E (a polar derivative) reduced mitochondrial damage/dysfunction, NF-κB transcription molecule, and cytokine expression. MotVit E, which accumulates inside mitochondria, had a more efficient protective effect on genes linked to TLRs [60] . The treatment of animals with vitamin E in the model of acute sepsis also showed beneficial effects [61] .…”
Section: Therapeutic Strategiesmentioning
confidence: 98%
“…Since organ dysfunction associated with sepsis is due, at least in part, to mitochondrial dysfunction and mitochondrial dysfunction is considered as main cause of oxidative stress in sepsis, antioxidants targeted to mitochondria have been considered as an efficient antioxidant protection in sepsis [ 12 ]. Minter et al [ 13 ] compared the positively charged antioxidant MitoVitE, which accumulates within mitochondria, with the membrane-bound α-tocopherol and water-soluble cytosolic Trolox with regard to their effects on oxidative stress, mitochondrial function and expression of key genes and proteins involved in the toll-like receptor (TLR)-2 and -4 inflammatory signalling pathways in the umbilical vein endothelial cell line HUVEC-C under conditions mimicking acute bacterial sepsis. Each of these three forms of vitamin E (5 μM each) was found to have similar reducing effects against induced oxidative stress and NFκB activation caused by exposure to lipopolysaccharide/peptidoglycan G. However, in difference to α-tocopherol and Trolox, MitoVitE had also widespread downregulatory effects on gene expression involved in TLR pathways, resulting in anti-inflammatory profile.…”
mentioning
confidence: 99%